Pembangunan Ekonomi Berbasis Blue Economy Pada Pariwisata Bali - Diputra, Gde Indra Surya; Kawiana, I Gede Putu; Pratiwi, Komang Ary; Saraswathi, Ida Ayu Anggawulan (PT Mattawang Mediatama Solution, 2025)
This project aims to investigate Blue Economy-Based Economic Development within Bali's tourism sector. This study employs a systematic review design, specifically a literature review that evaluates high-quality journals filtered by inclusion criteria, employing databases such as Google Scholar, Science Direct, and ResearchGate for its research. A search of papers from 2017 to 2024 yielded 142 results pertaining to the phrase